The Role of Technology in Employee Training and Development: A Systematic Review of Recent Advances and Future Directions - Leuhery, Ferdy (Penelitian dan Pengembangan Ilmu, 2024)
This systematic review explores the role of technology in employee training and development, focusing on its impact on training effectiveness and organizational growth. Through analysis of various literature, this research identifies technology adoption in training as a key factor in enhancing accessibility, personalization, and efficiency of the learning process. Furthermore, findings highlight the role of mediating factors such as technological competence, organizational support, and employee motivation in strengthening the relationship between technology adoption and training effectiveness. Practical and theoretical implications of these findings are outlined, along with recommendations for further development in this domain.